GAYA KOMUNIKASI EQUALITARIAN DAN DYNAMIC DALAM MEMBANGUN KEAKTIFAN BELAJAR AWARDEES IISMA 2024 - Ahmad Faruq Baihaqi; Fajar Hariyanto; Rastri Kusumaningrum (Halu Oleo University, 2025)
Recognising that dynamic lecturer-student interaction profoundly influences learning effectiveness in multicultural environments, this study aims to analyse lecturers' communication styles in fostering engagement among IISMA 2024 awardees at Prince of Songkla University, Thailand. Using a qualitative descriptive method, data were gathered from the Faculty of Management Sciences, Bachelor of Business Administration Program lecturers via semi-structured online interviews, moderate participant observation, and literature review. Results indicate that lecturers primarily employ Equalitarian and Dynamic communication styles. These styles successfully cultivate an equitable, interactive, and supportive learning environment, encouraging active student participation in expressing opinions, asking questions, and collaborating on projects.